The woman who lost her soul and other stories - Mireles, Jovita González, 1904-1983 (Recovering the U.S. Hispanic Literary Heritage Project publication., 2000)
The writer Jovita Gonzalez was long a member and ultimately served as president of the Texas Folklore Society, which strove to preserve the oral traditions and customs of her native state. Many of the folklore-based stories in this volume were published by Gonzalez in periodicals such as the Southwest Review from the 1920s through the 1940s but have been gathered here for the first time.Sergio Reyna has brought together more than thirty narratives by Gonzalez and arranged them into Animal Tales (such as The Mescal-Drinking Horse); Tales of Humans (The Bullet-Swallower); Tales of Mexican Ancestors (Ambrosio the Indian); and Tales of Ghosts, Demons, and Buried Treasure (The Woman Who Lost Her Soul). Reyna also provides a helpful introduction that succinctly surveys the author's life and work and considers her writings within their historical and cultural contexts.